Pengaruh Penggunaan Jenis Mulsa terhadap Sifat Fisik Tanah dan Laju Pertumbuhan Tanaman Tomat (Lycopersicum esculentum L.) - I Kadek Dwi Adi Saputra; I Wayan Tika; Ni Luh Yulianti (Jurnal BETA (Biosistem dan Teknik Pertanian), 2021)
Soil processing intensively without paying attention to factors which affect it such as the lack of nutrients, unbalance fertilization decreases physical quality of the soil. Therefore, soil processing is necessary to the growing condition of the tomato plants and improve nutrient availability for plants. The aims of the research are to determine the changes in soil physical properties due to the use of mulch types in line with the age of tomato plants and determine the effect of the use of mulch types on the rate of growth of tomato plants. This research is conducted with a completely randomized design with treatment without mulch, silver plastic mulch, black plastic mulch, transparent UV plastic mulch, and rice straw mulch. Each handling 15 times. The results show that the ground water content of 2 week after planting was 13-35%, 4 week after planting 20-42%, 6 week after planting 23-44%, 8 week after planting 27-51%, 10 week after planting 26-53%, 12 week after planting 32-63%. Average soil organic matter 1.16% with low category. Average permeability of land is 4.13 cm/hour in the slow to moderate category. Treatment without mulch significantly affected to the soil porosity with an average value of 48% in the less grade. The average value of the number of leaves in the silver plastic mulch treatment 122.89 strands and 124.83 strands of rice straw. The dry weight value of tomato plants in the treatment of rice straw mulch 205.87 grams and in the treatment of transparent UV plastic mulch 118.33 gram.